Characterization and expression of the human rhoH12 gene product. - Avraham, H (1989)
The rho genes constitute an evolutionarily conserved family having significant homology to the ras oncogene family. These genes have been found in Saccharomyces cerevisiae, Drosophila melanogaster, rat, and human; their 21,000-dalton products show strong conservation of structure. In humans, three classes of rho cDNA clones have been identified which differ by virtue of the presence of variable C-terminal domains: rhoH12, rhoH6, and rhoH9. The predicted 193 amino acids of human rhoH12 protein show 88% similarity with those of the human rhoH6 clone, 96.8% similarity with those of the Aplysia rho product, and 81.8% similarity with those of the yeast RHO1 protein. Rat-1 and NIH 3T3 mouse fibroblasts were transfected with clones containing the normal human rhoH12 allele as well as the variants encoding valine in place of the glycine and leucine in place of the glutamine normally found at residues 14 and 64, respectively. These replacements mirror the changes responsible for oncogenic activation of the related ras-encoded p21 proteins. These mutant rhoH12 clone alleles did not cause focus formation in monolayers or growth in soft agar. However, amplification of normal rhoH12 via cotransfection with a dihydrofolate reductase gene resulted in colonies that displayed reduced dependence on serum for growth, grew to higher saturation densities, and were tumorigenic when inoculated into nude mice. Normal p21rho protein was detected in the transfected cell lines as well as in normal cell lines by Western immunoblot and immunoprecipitation analysis with rabbit antibodies raised against the peptide corresponding to amino acids 122 to 135.